Provision of the airplane safety with the account of air flowing between compartments - Donik, V. D. (Proceedings of National Aviation University (archive), 2003)
The mathematical model of definition of parameters of air inside a compartment is developed in view of parameters of feed and discharge air. Comparison of results of calculation and experiment is carried out. The process of air flowing between compartments is investigated and the main regularities of influence ofparameters of a moving flow on a structure of a compartment andpeople are determined